2020
DOI: 10.1007/s10741-020-10038-w
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2-inhibitors; more than just glycosuria and diuresis

Abstract: Heart failure (HF) continues to be a serious public health challenge despite significant advancements in therapeutics and is often complicated by multiple other comorbidities. Of particular concern is type 2 diabetes mellitus (T2DM) which not only amplifies the risk, but also limits the treatment options available to patients. The sodium-glucose linked cotransporter subtype 2 (SGLT2)-inhibitor class, which was initially developed as a treatment for T2DM, has shown great promise in reducing cardiovascular risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 107 publications
0
60
0
8
Order By: Relevance
“…Secondary analyses of the EMPA-REG OUTCOME trial (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients) indicate that CV and kidney function benefits are unlikely mediated by the glucose-lowering properties of the SGLT2 inhibitors (Inzucchi et al 2018 ). The cardiorenal syndrome is critical in HF management, which could be directly addressed by SGLT2-inhibitors (Fathi et al 2020 ). As discussed above, the outcomes of different clinic trials show the co-existence of CV and renal protection, indicating the involvement of other non-glycemic pathways by SGLT2 inhibition (Bell and Yellon 2018 ).…”
Section: Mechanistic Perception Of Sglt2 Inhibitor and Na/k-atpasementioning
confidence: 99%
“…Secondary analyses of the EMPA-REG OUTCOME trial (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients) indicate that CV and kidney function benefits are unlikely mediated by the glucose-lowering properties of the SGLT2 inhibitors (Inzucchi et al 2018 ). The cardiorenal syndrome is critical in HF management, which could be directly addressed by SGLT2-inhibitors (Fathi et al 2020 ). As discussed above, the outcomes of different clinic trials show the co-existence of CV and renal protection, indicating the involvement of other non-glycemic pathways by SGLT2 inhibition (Bell and Yellon 2018 ).…”
Section: Mechanistic Perception Of Sglt2 Inhibitor and Na/k-atpasementioning
confidence: 99%
“…Recent clinical studies demonstrated favorable cardiovascular effects of the antidiabetic drugs from the sodium-glucose cotransporter 2 (SGLT2) inhibitor class, including a reduction of cardiovascular death, non-fatal myocardial infarction (MI), heart failure, and non-fatal stroke, as well as all-cause mortality [ 1 , 2 , 3 , 4 , 5 , 6 ]. In experimental models, cardiac contractility was improved in heart failure with preserved and reduced ejection fractions [ 7 , 8 , 9 , 10 , 11 ], in ischemia/reperfusion [ 12 ], MI models [ 13 , 14 , 15 , 16 , 17 ], and diabetic cardiomyopathy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SGLT-2 inhibitors decrease plasma glucose levels and thus the availability of glucose as a myocardial energy source, which necessitate the use of alternative sources such as ketone bodies and BCAAs for cardiac energy metabolism. This mild hyperketonic state provides a more efficient energy source by creating an overall reduction in oxygen consumption and improvement cardiac function 18,32,33. Evidence to support this theory has been demonstrated in animal models treated with empagliflozin, which resulted in a reduction of left ventricular mass and improvements in left ventricular function 32,34…”
Section: Proposed Cardioprotective Mechanismsmentioning
confidence: 96%
“…Cardiac muscle is capable of using various substrates in order to make metabolic energy in the form of adenosine triphosphate (ATP). This is achieved primarily via metabolism of free fatty acids (FFAs), while glucose, ketone bodies, and branched chain amino acids (BCAAs) are used to a lesser extent under normal physiological conditions 18,32,33. In the setting of heart failure, the metabolic flexibility of the heart is lost and cardiac tissue favors glucose oxidation for energy production instead of FFAs, ketone bodies, or BCAAs, which, in turn, increases oxidative stress and further impairs left ventricular function 32,33.…”
Section: Proposed Cardioprotective Mechanismsmentioning
confidence: 99%